(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2020)
PAHs (polycyclic aromatic hydrocarbons) in atmosphere are amongst the hazardous identified organic pollutants. The present study was conducted on the determination of PAHs concentrations in the air of Data Darbar Chowk, Lahore, Pakistan. The particulate matters in the atmosphere were collected using high volume samplers. Average Total Particulate Matter (mg) of PM2.5was 20.96 and PM10was 188.7. The concentration of PM2.5was 698.81 ngm-3/hr and 16771 ngm-3/day while concentration of PM10was 6290 ngm-3/hr and 150960 ngm-3/day. Quantification of different PAHs and related compounds was done by using Gas Chromatography. The mean total quantity of PAH in air was 955.588 ngm-3. The mean concentration of dibenzo (a, h) anthracene was highest i.e. 161.33 ngm-3with 13.94 ngm-3 Minimum and 308.72 ngm-3Maximum, concentrations. PAHs concentration was found to be very high in current research. There should be proper control through air management system to tackle with harmfulness of health hazardous organic pollutants. Bangladesh J. Sci. Ind. Res.55(2), 147-152, 2020